Pembuatan Kalsium Laktat dari Batu Kapur Bukit Tui Padang Panjang - Zulharmita Zulharmita; Roslinda Rasyid; Wessi Anhar (Jurnal Farmasi Higea, 2015)
A study concerning the manufacture of calcium lactate from the limestone hills Tui Leopold. Limestone sample of  30 g was dissolved in 6 M HCl, filtered and the filtrate was added 6 M NH4OH to pH 10. Then added lactic acid 1 M. The precipitate is filtered, washed, dried in an oven at a temperature of 1050 C. The results obtained calcium lactate as 6. 2084 g. To determine the calcium content in limestone identification and assay of calcium, limestone is used as much as 1 g of calcium levels and obtained percentage is 36.08 %. Examination of limestone calcium lactate include organoleptic examination, solubility, qualitative identification, examination and the melting point of the assay by the method complexometry. The third difference in the weight of calcium lactate calcium percentage of the results obtained, for a weight of 1 g as much as 77.13 % w/w , weight of 2 g as much as 90.28 % w/w, while the weight of  3 g as much as 81.42 % w/w. From the data of calcium lactate assay with a sample of 7.93 g drying results have calcium levels that the percentage purity 82.94 % w/w, and the results of testing the melting point is 2280 C calcium lactate. So natural limestone hill Tui Leopold has a high purity calcium levels that can be made of calcium lactate.